The Effect of Digital Literacy on Learning Outcomes and 21st Century Skills of High School Students: Systematic Literature Review - Rianzah Munawaroh; Eni Noviani; Sudarmiatin Sudarmiatin; Mokhammad Nuruddin Zanky (International Forum of Researchers and Lecturers, 2025)
This study aims to systematically examine the influence of digital literacy on the learning outcomes and 21st-century skills of high school students. The method used is a Systematic Literature Review (SLR) following the PRISMA guidelines. Data sources were obtained from various academic databases, including Google Scholar, ERIC, ScienceDirect, and SpringerLink, with publications ranging from 2019 to 2025. A total of 30 articles were selected based on predetermined inclusion and exclusion criteria. The analysis was conducted using a thematic approach to identify patterns, relationships, and the contribution of digital literacy to learning outcomes and the development of 21st-century skills, such as critical thinking, collaboration, communication, and creativity. The synthesis results show that digital literacy has a significant influence on improving learning outcomes and strengthening 21st-century competencies. This study emphasizes the importance of integrating digital literacy into secondary school curricula and teacher training to support effective 21st-century learning.